Circadian and seasonal variation of the body temperature of sheep in a tropical environment. - daSilva, R. G.; Minomo, F. R. (Springer, 1995)
Nychthemeral and annual rhythms of the rectal temperature were determined for Corriedale sheep in a tropical climate. The minimum rectal temperature averaged 39.55 degrees C at 0500 hours in summer, and 38.87 degrees C at 0600 hours in winter. The maximum was 40.03 degrees C in summer (1700 hours) and 39.33 degrees C in winter (1830 hours). Annual cycle of the rectal temperature showed a minimum in July and maximum in December.
Keywords: animal; body temperature; circadian rhythm; male; periodicity; physiology; season; sheep; tropic climate; Animals; Body Temperature; Circadian Rhythm; Male; Periodicity; Seasons; Sheep; Tropical Climate